An Exhaustive Search Algorithm for Finding Hamiltonian Cycles - Zeps, Dainis (EIK,Elektronische Informationsverarbeitung und Kybernetik, Universität Trier, Akademie Verlag, 1980)
The paper suggests an exhaustive search algorithm for finding Hamiltonian circuits in an undirected graph based on depth-first search and working successfully on sparse graphs. The method is based on the idea not to search all palms in the graphs but only those which are not branched. Tutte's 46 vertices graph searching took less than 3 minutes on EC- 1022 computer.
Keywords: graph theory; hamiltonian cycle; depth-first search; palm tree